Does Financial Liberalization Improve the Allocation of Investment?: Micro Evidence from Developing Countries - Arturo Galindo; Fabio Schiantarelli; Andrew Weiss (Inter-American Development Bank, Research Department, 2002)
Has financial liberalization improved the efficiency with which investment funds are allocated to competing uses? In this paper, we address this question using firm-level panel data from 12 developing countries. We develop a summary index of the efficiency of investment allocation that measures whether, and to what extent, investment funds are going to firms with a higher marginal return to capital. We then examine the relationship between this index and various measures of financial liberalization. The results suggest that in the majority of cases financial reform has led to an increase in the efficiency with which investment funds are allocated.
Keywords: 330; Finanzmarktregulierung; Investition; Allokationseffizienz; Entwicklungsländer